Teaching Science Using Metacognitive Strategies to Improve Achievement - Wagaba, Francis; Treagust, David; Koul, Rekha (SEAMEO RECSAM, 2011)
This action research study was designed to evaluate the effectiveness of a repertoire of interventions aimed at enhancing secondary school students’ metacognitive capabilities in science and the correlation between the students’ metacognitive capabilities and their results in science tests and assignments. The action research, which started in 2009, involved 2 cycles. In the first cycle, 35 students from Year 9 participated in the action research. The interventions included providing students with clearly stated focused outcomes, engaging in collaborative group work and using concept mapping. In the second cycle, a total of 57 students from Years 7, 9 and 11 participated. The same interventions, as in cycle one, were employed in addition to using reflection journals. In the first cycle, the data to evaluate the effectiveness of the metacognitive interventions were obtained from pre- and posttests on metacognitive questionnaires and pre-and posttests scores using two-tier tests in three different science topics. The results of the metacognitive survey showed gains on Metacognitive Support but not for Metacognitive Strategy Use. Student gains were evident from the test scores for Light and Atoms.